PENGEMBANGAN MODUL PEMBELAJARAN DAN LATIHAN GULAT BERBASIS GERAK MULTILATERAL DI KABUPATEN KARO - Jan Bobby Nesra Barus; Julius Boy Nesra Basgimata Barus (Universitas Quality, 2021)
Wrestling is one of the sports of achievement that requires a specialized training program, but before achieving that it is more important to prepare the basic foundations of young wrestlers by designing a training program that includes overall development or what is known as a multilateral-based training program. This study aims to develop a multilateral motion-based wrestling learning and training module in Karo District. Data analysis was carried out using qualitative data analysis techniques, while questionnaire analysis, product validation, and testing of athletes included: changing qualitative data to quantitative, tabulating all data obtained in each aspect, calculating the average score, and changing the score. average into categories. The results showed that the quality of the developed learning modules based on the evaluation of material experts were